Monitoring of Plankton Spatial and Temporal Characteristics With the Use of a Submersible Digital Holographic Camera - Dyomin, Victor; Davydova, Alexandra; Morgalev, Sergey; Kirillov, Nikolay; Olshukov, Alexey; Polovtsev, Igor; Davydov, Sergey (Frontiers in Marine Science, 2020)
The study shows that the use of a submersible digital holographic camera as part of a multifunctional hardware and software complex allows carrying out in situ measurements of plankton, automating the process of obtaining data on plankton, as well as classifying plankton species up to an order within the specified taxonomic groups. Such automation ensures monitoring expeditionary or stationary research of species diversity and spatial and temporal organization of zooplankton in conjunction with hydrophysical parameters of the medium. This paper presents the full-scale results of vertical profiles and daily measurements of plankton made with the use of the submersible digital holographic camera, as well as the classification of plankton in laboratory and field conditions in the automatic mode. It is shown that within the accomplished version the classification algorithm using the morphological parameter makes it possible to solve the problem quickly (time required to obtain the result is less than 1 second and depends on the number of plankton particles and the frame size of a restored image), however the classification accuracy by orders varies within 50-60%.